Learning Strategies Used by ESL Students in Learning English at Capiz National High School, Philippines - Hardiyanto, Asep; Nastika MN, Ovalia; Eslabon, Marica Nilda A.; Suprapto, Irawan (JEELS (Journal of English Education and Linguistics Studies), 2024)
Learning strategies encompass deliberate techniques and methods employed by individuals to optimize their acquisition and comprehension of information or skills. Among the categories of language learning strategies frequently utilized are memory, cognitive, compensatory, metacognitive, affective, and social strategies, all of which serve as valuable tools for enhancing language acquisition efficiency. Consequently, this study aims to assess the utilization level of language learning strategies, determining the extent to which students employ these strategies, and identifying the most and least utilized strategies in learning English. For data collection, this research adopted Oxford's Strategy Inventory Language Learning (SILL) questionnaire version 7.0. Employing quantitative descriptive methods, data were gathered from 42 Capiz National High School ESL students. The findings revealed a tendency among students to utilize strategies in their English learning endeavors, with cognitive strategies being the most frequently employed and affective strategies being the least used. These results underscore the importance for ESL teachers to tailor teaching methods, materials, and activities to align with students' preferred strategies, thereby supporting language learning effectively. Additionally, future studies are recommended to utilize larger and more diverse samples to further explore the relationships between learning strategies and other variables in greater depth.